1982
DOI: 10.1021/jf00114a051
|View full text |Cite
|
Sign up to set email alerts
|

Additional aroma components of honeydew melon

Abstract: results in a higher rate of protein free radicals formation, as already mentioned; (2) lipid hydroperoxide decomposition either as a complex [LOOH-PH] or as LOOM; both decompositions would promote protein free radical formation and subsequent protein polymerization in accordance with the proposed mechanism; the decreases of the PV of the lysozyme-lipid emulsions subjected to freezedrying support this hypothesis.Lysozyme biological activity decreases after treatment with peroxidizing lipids. Previous works (Kan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 5 publications
0
66
0
1
Order By: Relevance
“…However, 'Earl's Together' melon herein produced only a trace of ethylene, but ester compounds were accumulated at later stages of maturity and ADH and AAT acitivities were up-regulated to some degrees. Furthermore, even though there has been no report examing volatile changes of a non-climacteic type during ripening, esters have long been reported in many non-climacteric type melons (Buttery et al, 1982;Kourkoutas et al, 2006;Moshonas et al, 1993;Yabumoto et al, 1978). Accordingly, aroma formation like softening should be categorized as a partially ethylene dependent phenomenon.…”
Section: Research Reportmentioning
confidence: 99%
“…However, 'Earl's Together' melon herein produced only a trace of ethylene, but ester compounds were accumulated at later stages of maturity and ADH and AAT acitivities were up-regulated to some degrees. Furthermore, even though there has been no report examing volatile changes of a non-climacteic type during ripening, esters have long been reported in many non-climacteric type melons (Buttery et al, 1982;Kourkoutas et al, 2006;Moshonas et al, 1993;Yabumoto et al, 1978). Accordingly, aroma formation like softening should be categorized as a partially ethylene dependent phenomenon.…”
Section: Research Reportmentioning
confidence: 99%
“…Many esters were identifi ed in honeydew melon by solid-phase microextraction and GC-MS analysis. [27] Similarly, Buttery et al [18] studied the volatile components of honeydew melon and found many esters, including (Z)-3-nonenyl acetate, (Z)-6-nonenyl acetate and (Z,Z)-3,6-nonadienyl acetate. Previous research has shown that less climacteric melons, such as honeydew, produce less ethylene and thus a smaller quantity of esters than the climacteric muskmelons, e.g.…”
Section: Volatile Composition Of Honeydew Melonmentioning
confidence: 99%
“…After all, (Z)-3-nonenyl acetate, (Z)-6-nonenyl acetate and (Z,Z)-3,6-nonadienyl acetate have been found in honeydew melon and (Z)-6-nonenyl acetate possessed a pleasant honeydew melon-like aroma. [18] The sensitivity and selectivity of GC-MS analysis has drastically improved over the years, especially with MS/MS techniques. We decided to attempt trace level target analysis of (E,Z)-2,6-nonadienyl acetate in the aroma extract via GC-MS/MS techniques in order to verify our hypothesis, because this compound could impact the aroma of honeydew melon at a higher concentration.…”
Section: Volatile Composition Of Honeydew Melonmentioning
confidence: 99%
“…All of the aromatic volatiles identifi ed by Saftner et al ( 2008 ) had been previously reported in melons (Beaulieu and Lea 2006;Buttery et al 1982 ) . Distinct qualitative and quantitative differences were found in aromatic volatiles among melon genotypes (Wyllie et al 1994 ) with concentrations of many volatiles, particularly the more abundant esters, being generally higher in cantaloupe than in honeydews (Wyllie and Leach 1992 ;Yabumoto et al 1978 ) .…”
Section: Nutritive/medicinal Propertiesmentioning
confidence: 67%